Low-Cost and Simple Frontal Sinus Surgical Cutting Guide Modeling for Anterior Cranioplasty in Facial Feminization Surgery: How To Do It - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Background: This study demonstrates a novel and simple design to create a low cost frontal sinus surgical cutting guide, using patient's frontal sinus cavities as references, to perform an anterior cranioplasty in facial feminization surgery. A clinical series demonstrates its clinical use and safety. Material and Methods: Authors used a 4 open-source software protocol for the virtual surgical modeling (VSP). Retrospectively, pre- and post-operative complications were reviewed, and a FACEQ questionnaires were used to evaluate patient's postoperative Satisfaction with forehead and eyebrows.'' Recordings of the VSP and surgical technic are presented. Results: Sixteen patients were operated between November 2018 and November 2020 using in-house surgical guides. All were performed by authors in 5 to 10 minutes using Blender open-source Software. No complications were reported and authors always found an optimal retention of the surgical guide on the convex bony surface of the forehead and frontonasal area. FACE-Qquestionnaire reported a very high satisfaction for all patients (mean score: 22/24). Discussion: This simplify organic design can be performed efficiently by any surgeon even without previous training in home staging VSP. Patient satisfaction was very high, along with an absence of postoperative complications.
Keywords: Anterior cranioplasty; facial feminization surgery; open-source software; virtual surgical planning; OPEN-SOURCE SOFTWARE; RECONSTRUCTION; FOREHEAD